Intracellular distribution of input vesicular stomatitis virus proteins after uncoating. - Rigaut, K D (1991)
We have examined the fate of input viral proteins following the uncoating of vesicular stomatitis virus (VSV) by immunofluorescence microscopy, immunoelectron microscopy, and cell fractionation. VSV was adsorbed to BHK cells and allowed to become internalized in the presence of 100 mM NH4Cl; the NH4Cl was then removed to initiate synchronized uncoating. The three major structural proteins of VSV, the matrix protein (M), the nucleocapsid protein (N), and the glycoprotein (G), were each distributed uniquely after uncoating. Immunofluorescence microscopy showed that both G and N proteins retained a punctate distribution, whereas M protein was diffusely distributed throughout the cytoplasm, suggesting that it had become soluble. Immunoelectron microscopy showed that N protein was found in clusters (presumably in intact nucleocapsids) associated with the cell cytoskeleton and in unfused virions in endosomes and lysosomes. M protein was found diffusely distributed throughout the cytoplasm and also in endosomes and lysosomes. G protein was found only in association with endosomes and lysosomes after uncoating. Electrophoretic analysis of the high-speed cytosol fraction from infected cells showed that it contained chiefly M protein. The amount of M protein in the cytosol increased continuously during 90 min of uncoating, confirming its solubilization during uncoating. M protein was not covalently modified by phosphorylation upon uncoating, as evidenced by its mobility on nonequilibrium pH gradient gel electrophoresis. We suggest that those nucleocapsids associating with the cytoskeleton after uncoating may represent the sites of primary viral transcription.